The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/hbm.25193
|View full text |Cite
|
Sign up to set email alerts
|

Individual resting‐state frontocingular functional connectivity predicts the intermittent theta burst stimulation response to stress in healthy female volunteers

Abstract: Intermittent theta burst stimulation (iTBS) delivered to the dorsolateral prefrontal cortex (DLPFC) has been investigated as a promising treatment for stress and stressrelated mental disorders such as major depression, yet large individual differences in responsiveness demand further exploration and optimization of its effectiveness. Clinical research suggests that resting-state functional connectivity (rsFC) between the DLPFC and the anterior cingulate cortex (ACC) can predict iTBS treatment response in depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Test (Pulopulos et al, 2020;Wandel et al, 2020) have shown a robust stress response, and current results also show a significant decrease in HRV from baseline to speech task, and a significant increase in subjectively experienced negative emotion and physical sensations. Third, there is continued debate around respiratory influences on HRV and controlling for this (Laborde et al, 2017).…”
Section: Discussionsupporting
confidence: 56%
“…Test (Pulopulos et al, 2020;Wandel et al, 2020) have shown a robust stress response, and current results also show a significant decrease in HRV from baseline to speech task, and a significant increase in subjectively experienced negative emotion and physical sensations. Third, there is continued debate around respiratory influences on HRV and controlling for this (Laborde et al, 2017).…”
Section: Discussionsupporting
confidence: 56%
“…The results of Tik et al ( 33 ) confirmed the earlier findings from Fox et al ( 8 , 9 ); namely that the functional connectivity between the stimulation site in the left DLPFC and the subgenual part of the ACC are relevant for rTMS treatment efficacy for depression subjects. In another functional connectivity study, including only healthy subjects, it was also shown that individual resting‐state functional connectivity between left DLPFC and caudal ACC was linked to a larger attenuation of stress‐system sensitivity during active, but not during sham iTBS ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“… Stress : N/A Stress : ↑ stress and tension (VAS), ↓ happiness (VAS) Stress : ↓ HRV N/A No interaction effect (VAS) No interaction effect (HRV or salivary cortisol) 2 groups (active vs. sham) 2. Stressor dlPFC (left) Sham: Yes Control: None (1 session) - Adjusted BeamF3 algorithm NIBS : N/A NIBS : None NIBS : ↓ AUCi after active TMS (vs. sham) de Wandel et al, 2020 18–27 yrs (N = 34) Within subjects crossover (active vs. sham) 1. Stressor rTMS/ 50 Hz (burst freq 5Hz) 110% RMT 54 cycles, 10 burst of 3 pulses, train duration of 2s, ITI of 6 s 1620 pulses 2 sessions of 5mins Stress : N/A Stress : Cannot be assessed Stress :↑ cortisol N/A No interaction effect (VAS) No interaction effect (cortisol) Control: None 2.…”
Section: Effects Of Neuromodulationmentioning
confidence: 99%
“…Of the 11 studies targeting the left dlPFC, 9 found a main effect of stressor (TSST, CFT, or cyberball) on at least one mood measure ( Baeken et al, 2014 , 2018 ; De Raedt et al, 2017 ; De Smet et al, 2021 ; De Witte et al, 2020 ; Fitzgibbon et al, 2017 ; Remue et al, 2016 ). Five of those studies used the TSST ( Carnevali et al, 2020 [tDCS]; De Witte et al, 2020 [rTMS]; Pulopulos et al, 2019 ; 2020 [rTMS]; Wandel et al, 2020 [rTMS]) and only one found any effects of neuromodulation: Carnevali et al, 2020 used anodal tDCS on the left dlPFC; the group that received tDCS reported lower anxiety after stressor compared to sham. Four studies used critical feedback as the stressor; although all found a main effect of stressor on at least one mood measure, none found any effects of neuromodulation on mood ( Baeken et al, 2014 [tDCS]; Baeken et al, 2018 [tDCS]; De Raedt et al, 2017 [tDCS]; Remue et al, 2016 [tDCS]).…”
Section: Effects Of Neuromodulationmentioning
confidence: 99%